2020
DOI: 10.1093/jn/nxaa282
|View full text |Cite
|
Sign up to set email alerts
|

High Consumption of Red Meat Is Associated with Excess Mortality Among African-American Women

Abstract: Background Red meat is a rich source of nutrients but is typically high in saturated fats. Carcinogenic chemicals can be formed during cooking and processing. Little is known about the relation of red meat consumption to mortality in African Americans (AAs), a group with excess mortality and high consumption of red meat relative to whites. Objective Our objective was to assess the association between red meat consumption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 55 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…For processed meat, these values were 0.96 (0.71 ,1.29) and 0.95 (0.77 ,1.18), respectively. Our study builds upon prior evidence in AA adults (31) by examining individual CVD events including CHD, stroke, and heart failure, as well as total CVD.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…For processed meat, these values were 0.96 (0.71 ,1.29) and 0.95 (0.77 ,1.18), respectively. Our study builds upon prior evidence in AA adults (31) by examining individual CVD events including CHD, stroke, and heart failure, as well as total CVD.…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge only one other study has investigated the prospective associations between red and processed meat consumption and CVD outcomes, specifically among AA adults. Using 22 y of follow-up data from the Black Women's Health Study, a large cohort of AA women living across the US, Sheehy et al (31) found that each serving per day increase in unprocessed red and processed red meat intakes were associated with 9% [HR = 1.09 (CI: 1.00, 1.18)] and 14% [1.09 (CI: 1.07, 1.21)] greater risk of CVD mortality, respectively. Although CVD mortality was not examined in the present study, we observed that neither CVD (non-fatal and fatal) or CHD was associated with unprocessed red meat or processed meat intake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations